Is the remedy worse than the disease? On concentrations, monopolies and access to medicines: Sobre concentraciones, monopolios y acceso a los medicamentos - Huarag Guerrero, Enrico Marcel (2018)
The recent case of the purchase of Quicorp S.A. (owners of the chain of pharmacies Mifarma) by InRetail (owners of the chain of pharmacies Inkafarma) has led to raise the need for a law to control mergers and acquisitions, in order to avoid the consolidation of monopolies or positions of domain in the pharmaceutical market. However, our legal system does not prohibit monopolies or market dominance positions, and the aforementioned merger does not represent a position of market dominance. On the other hand, if there is cause for concern about the existence of another type of monopoly, the one represented by the patents. This article points out some alternative solutions to the problems that have arisen in the Peruvian pharmaceutical market.